Crafted Worlds, Imagined Pasts: Fantasy, Gaming and Archaeology (AmS-Skrifter, 2026)
Since the 1970s, fantasy gaming has grown from a small niche hobby to a global multi-billion-dollar industry. Whether played around a tabletop or online, millions of people, including many archaeologists, immerse themselves in imagined worlds or pasts during their spare time. There is no doubt such games provide much-needed enjoyment and escapism for their players. But do some of them also hold the potential to yield real insights into past societies, and can they help us get just a little closer to the lived experiences of our ancestors and the societies and worlds they inhabited? The modern gaming hobby and industry may be a very recent phenomenon, but the human imagination, and mythologies and cosmologies that include the fantastic, are ancient aspects of the human condition; does the fantasy genre, and roleplaying games specifically, have the potential to provide genuine insights into the past?This paper explores such questions. It considers both the value of gaming for those already engaged in the serious study of the past, as well as the potential that the hobby offers as a gateway to an interest in archaeology and history for the millions of gamers worldwide.